WEBSITE MAKING RESTAURANT & CAFE DE LA Rossa RESTAURANT using Macromedia Flash MX, PHP AND MySQL - Ahmad Mursyidi; Marzuki Skom, MMSi (Jurnal Sistem Informasi, 2007)
Scientific Writing is about making Website De La Rossa Cafe & Restaurant usingMacromedia Flash MX, PHP and MySQL where the writing is addressed to the public toprovide information about La Rossa Cafe & Restaurant Restaurant by promoting it bycreating a website about the product portfolio by La Rossa Cafe & Restaurant such asfood, banqueting, and various wines on offer.